2020
DOI: 10.1016/j.neuroimage.2020.117358
|View full text |Cite
|
Sign up to set email alerts
|

Multi-centre, multi-vendor reproducibility of 7T QSM and R2* in the human brain: Results from the UK7T study

Abstract: Introduction We present the reliability of ultra-high field T 2 * MRI at 7T, as part of the UK7T Network's “Travelling Heads” study. T 2 *-weighted MRI images can be processed to produce quantitative susceptibility maps (QSM) and R 2 * maps. These reflect iron and myelin concentrations, which are altered in many pathophysiological processes. The relaxation parameters of human brain tissue are such that R … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 80 publications
2
29
0
Order By: Relevance
“…Second, QSM is known to be affected by the subjects’ head orientation with respect to the main magnetic field. In a recent study [ 39 ], such dependence was reported to be about 0.01 ppm per 5° in the deep brain region. Since the head orientation was not controlled in our study, such orientation dependence could have added to the overall variability of our QSM results (Supplementary Material 3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, QSM is known to be affected by the subjects’ head orientation with respect to the main magnetic field. In a recent study [ 39 ], such dependence was reported to be about 0.01 ppm per 5° in the deep brain region. Since the head orientation was not controlled in our study, such orientation dependence could have added to the overall variability of our QSM results (Supplementary Material 3).…”
Section: Discussionmentioning
confidence: 99%
“…Since the head orientation was not controlled in our study, such orientation dependence could have added to the overall variability of our QSM results (Supplementary Material 3). Lastly, while R2* was calculated with a relatively robust method of voxel-wise fitting of the magnitude data, QSM was primarily based on the image phase, which is more prone to errors due to physiological motion and streaking artifacts [ 38 , 39 ]. Along with the small sample size, such increased variability may have rendered QSM weak in its statistical power to distinguish between different subject groups.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, no dedicated B 0 and B 1 correction or correction for gradient delays was performed. Susceptibility mapping has been shown not to depend on B 1 inhomogeneties even in multi-center ultra-high field studies QSM ( Rua et al, 2020 ; Voelker et al, 2021 ), but the correction of dynamic B 0 fluctuations improves image quality in susceptibility-based methods and could thus enable a better characterization for multi-contrast approaches including QSM segmentation ( Jorge et al, 2020 ). However, MTR measurements are more sensitive to B 1 inhomogeneites and especially for multi-site studies, B 1 correction would be advisable ( Barker et al, 2005 ).…”
Section: Discussionmentioning
confidence: 99%
“…Alternative sequences have been used to observe changes in iron in the healthy brain and in disease (19,20) by measuring the T2* transverse relaxation time (or its inverse rate, R2*) or the local tissue magnetic susceptibly χ using quantitative susceptibility mapping (QSM) (21)(22)(23). Susceptibility weighted imaging (SWI) uses post-processing of T2*-w images, with the magnitude and filtered phase information providing image contrast from iron storage (24).…”
Section: Introductionmentioning
confidence: 99%